Improvement of an e-learning course with QFD analysis / Yoshida Masami (Penerbit UiTM (UiTM Press), 2008)
An investigational study was done through a blended PhD course; "Distance education and international cooperation in education" of Chiba University. Here, e-learning with LMS was used to provide lesson content, mentoring, discussion, assignment and learning activities using both Japanese and English to cover overall period of the course. And, the author introduced Quality Function Deployment (QFD) analysis to clarify proper measures for improvement of the course. QFD is a systematic process that helps us quickly understand and integrate our unintentional needs into the course. QFD enables to introduce integrated "tacit knowledge" into "procedural measures" by using decision making method, and also provides a transferable document that covers comprehension areas to related staff members.